Pendidikan Inklusi Untuk Anak Berkebutuhan Khusus di SD Negeri 2 Bengkala - Ananta, I Putu Rizky; Tamim, Imron Hadi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
This research focuses on the implementation of inclusive education for children with special needs at SD Negeri 2 Bengkala. The researcher analyzes how inclusive education is applied to children with special needs at SD Negeri 2 Bengkala using Abraham Maslow’s hierarchy of needs theory. The method used is a qualitative approach with a descriptive-explanatory type. The results of this study show that the inclusive education at SD Negeri 2 Bengkala initially aimed to meet the educational needs of the local community, namely the people of Bengkala Village, which is known as an Inclusive Village in the Province of Bali. The historical Bengkala Inscription mentions that the presence of the kolok (deaf individuals) in Bengkala Village was caused by an ancient curse. On the other hand, scientific findings have revealed that the high number of kolok individuals in the village is the result of endogamous marriage practices. SD Negeri 2 Bengkala implements an inclusive education system through special classes with various integrations. The analysis based on Maslow’s hierarchy of needs theory reveals that the inclusive education at SD Negeri 2 Bengkala can fulfill the basic needs of the “kolok” students, who currently number nine. In addition, inclusive education at SD Negeri 2 Bengkala also prepares the next level of education for the “kolok” students, ensuring the continuity of their educational journey. Keywords: Inclusive education, Kolok , Maslow's Hierarchy of Needs